Diastereoselective Synthesis of Morpholine Derivatives from Grignard Reagents and N-Sulfinyl Imines - Bateman, Joseph M.; Chan, Diana; Moroglu, Mustafa; Rahemtulla, Benjamin F.; Talbot, Eric P. A. (Synlett, 2021)
The stereoselective synthesis of substituted morpholine derivatives has been achieved through a two-step process involving diastereoselective addition of a Grignard reagent to a sulfinyl imine, followed by cyclization.
Keywords: morpholines; stereoselectivity; chiral auxiliaries; sulfinyl imines; Grignard reaction